VPS35 Deficiency or Mutation Causes Dopaminergic Neuronal Loss by Impairing Mitochondrial Fusion and Function - Fu-Lei Tang; Wei Liu; Jin-Xia Hu; Joanna Ruth Erion; Jian Ye; Lin Mei; Wen-Cheng Xiong (Cell Reports, 2015)
Vacuolar protein sorting-35 (VPS35) is a retromer component for endosomal trafficking. Mutations of VPS35 have been linked to familial Parkinson’s disease (PD). Here, we show that specific deletion of the VPS35 gene in dopamine (DA) neurons resulted in PD-like deficits, including loss of DA neurons and accumulation of α-synuclein. Intriguingly, mitochondria became fragmented and dysfunctional in VPS35-deficient DA neurons, phenotypes that could be restored by expressing VPS35 wild-type, but not PD-linked mutant. Concomitantly, VPS35 deficiency or mutation increased mitochondrial E3 ubiquitin ligase 1 (MUL1) and, thus, led to mitofusin 2 (MFN2) degradation and mitochondrial fragmentation. Suppression of MUL1 expression ameliorated MFN2 reduction and DA neuron loss but not α-synuclein accumulation. These results provide a cellular mechanism for VPS35 dysfunction in mitochondrial impairment and PD pathogenesis.